Tinjauan Yuridis Pengelolaan Limbah Medis di Rumah Sakit Umum Daerah Bung Karno Surakarta - Yudistira Yudistira; Lego Karjoko (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This study aims to determine the implementation of medical waste treatment at Bung Karno Hospital in Surakarta in accordance with Law Number 32 of 2009 concerning Protection and Management of the Environment and Government Regulation Number 101 of 2014 concerning Management of Hazardous and Toxic Waste. This study uses an empirical method and a statutory approach.The types of legal materials consist of primary and secondary.Primary legal materials is using laws, government regulations, and regional regulations of the province of Central Java. Secondary legal materials is using relevant books, journals and research. The author collected data by conducting observations and interviews with waste managers at the hospital. The results of this study are: The treatment of medical waste at Bung Karno Hospital is carried out in collaboration with external parties, this is because the hospital does not yet have its own incinerator. The implementation of liquid medical waste management, Bung Karno Hospital Surakarta, uses IPAL tanks and Redox AOP machines. The hospital has not properly implemented the regulations for B3 waste management.